Comparison of Seismic Site Factor Models Based on Equivalent Linear and Nonlinear Analyses and Correction Factors for Updating Equivalent Linear Results for Charleston, South Carolina - Nadarajah Ravichandran; Md. Ariful H. Bhuiyan; Vishnu Saketh Jella; Ashish Bahuguna; Jatheesan Sundararajan (Geosciences)
In practice, site-specific one-dimensional (1D) seismic site response analyses are conducted to compute surface acceleration time histories considering shear wave velocity profile, modulus reduction, damping, and site-specific ground motions. The computed surface responses depend not only on the geologic and seismic characteristics but also on the type of 1D analysis (i.e., equivalent linear or nonlinear) and the software. Equivalent linear analysis (EQLA) is preferred by practicing engineers because the analysis procedure is well defined, but the accuracy of the results is questionable for certain geologic and input motion characteristics. On the other hand, nonlinear analysis (NNLA) is accurate for any geologic and input motion characteristics, but it is complicated because certain steps in the analysis procedure are complicated and not well defined. The objective of this study is to compare the responses computed from EQLA and NNLA procedures and make recommendations on when to use EQLA and NNLA, considering Charleston, South Carolina; geology; and seismicity. About 18,000 NNLAs (DMOD2000 and DEEPSOIL) and EQLAs (SHAKE2000) were performed, considering variations in shear wave velocity profiles, shear modulus reduction curves, damping curves, and ground motions. Based on the results from each software, three seismic site factor models were developed and compared with the published models. Results show that the EQLAs produced conservative estimates compared to the NNLAs. It is also observed that the site factor model based on EQLA diverges from the models based on NNLA even at the lowest amplitude shaking considered in the study (0.05 g), particularly for profiles with low shear wave velocity. This indicates that soils behave nonlinearly even at low amplitude shaking. Although a similar shear stress/shear strain model is used in DMOD2000 and DEEPSOIL, the site factor models show significant differences. Finally, an easy-to-use chart was developed to select suitable software and analysis types for accurately computing the surface responses based on the peak ground acceleration (PGA) of the input motion at the reference rock outcrop and average shear wave velocity in the top 30 m.